Supply chain analysis: the case of an olive company (Research, Society and Development, 2022)
This research aims to analyze the OlivoPampa organization supply chain. It analyzes the four elements of the Supply Chain Management proposed by Aragão et al. (2004). In order to achieve that, a descriptive analysis is used, with a qualitative approach, through the case study method. Data was collected using semi-structured interviews, field diary and observation methods.The analysis of the results allowed us to identify the business processes used by the company, as they were built over time, there is access facilitation, due to the similarity with the wine supply chain. Regarding key members, the company has a long term partnership relation with suppliers, that chooses the supplier with the shortest delivery time. In addition, the company has good relationship with customers, who are attracted by reliability, product diversity, innovation, and the belief that performance could be improved. OlivoPampa does not share information with suppliers about stock and forecast purchases, since the sharing of information regarding future sales is done when necessary. The performance indicators used by the company are based on the number of complaints, order increase flexibility and stock level. In this way, it is possible to help the company OlivoPampa to have a more refined look at the supply chain, improving the management of the organization and its own supply chain, since the business relevance for Santana do Livramento county.